Tribulus terrestris Linn.: A Novel Natural Preservative for Improved Lipid Stability and Storage Quality of Meat Products - Noor, Sabahu; Bhat, Z. F.; Kumar , Sunil; Kalem , Insha Kousar (Journal of Meat Science, 2018)
A study was conducted to evaluate the potential of Tribulus terrestris as a novel natural preservative in meat products. Chevon sausages  were used as a model system and incorporated with different levels of T. terrestris viz. T1 (0.25%), T2 (0.50%) and T3 (0.75%) and were  vacuum packaged and assessed for various lipid stability and storage quality parameters under refrigerated (4±1OC) conditions. Sig nificantly (p
Keywords: Tribulus terrestris; Chevon Sausages; natural preservative; Lipid oxidation; Storage quality